Efficacy of Modified Bioactive Glass for Dentin Remineralization and Obstruction of Dentinal Tubules - Mahshid Saffarpour; Maryam Mohammadi; Mohammadreza Tahriri; Azadeh Zakerzadeh (Tehran University of Medical Sciences, 2017)
Objectives: This study assessed the efficacy of modified bioactive glass (MBG) for dentin remineralization and obstruction of dentinal tubules. Materials and Methods: Thirty-six dentin discs were made from 20 third molars and were stored in 12% lactic acid solution for two weeks to induce demineralization. The samples were divided into three groups (n=12): 1- BG, 2- BG modified with 5% strontium (Sr) and 3- BG modified with 10% Sr. After applying the BG, the samples were stored in artificial saliva for 7, 14 and 21 days. Attenuated Total Reflection-Fourier Transform Infrared Spectroscopy (ATR-FTIR), X-ray Diffraction (XRD) analysis, Scanning Electron Microscopy (SEM), and Energy-Dispersive X-ray (EDX) analysis were used to assess remineralization. Also, 6 dentin discs were divided into three groups of BG, BG modified with 5% Sr and BG modified with 10% Sr, to examine tubular occlusion. The discs were etched using 0.5M of EDTA for two minutes and were stored in artificial saliva for 7 days. Changes in dentin surface morphology were evaluated under SEM. Results: Group 3 showed high rates of remineralization at days 7 and 14, although the rate decreased at day 21. Group 2 exhibited high rates of remineralization at days 7, 14 and 21. Dentinal tubules were partially occluded by BG and BG modified with 5% Sr, while they were almost completely obstructed after the use of BG modified with 10% Sr. Conclusions: Strontium increases remineralization. Addition of 10% Sr to BG enhances apatite formation; however, the apatite dissolves over time. Addition of 5% Sr to BG stabilizes the apatite lattice and increases the remineralization.